PENENTUAN UMUR SIMPAN TERASI INSTAN DALAM KEMASAN - Mohammad Firdaus Nur Cahyo; Sri Hastuti; Iffan Maflahah (Agroindustrial Technology, University of Trunojoyo Madura, 2016)
Types of processed seafood is very popular in Indonesia is a shrimp paste. In general, the paste made of rebon, small fish, or anchovies and other additives. The weakness of the paste is a relatively short shelf life due to water levels are still high, so often grow mold during the storage process. The shelf life is not too long will become a problem for consumers. Therefore it is necessary for action to extend the shelf, one with the drying process so that it becomes an instant paste. Terasi instant in order to attract packed with a suitable container. The use of packaging can affect the quality and shelf life. Determining the shelf life of the product paste can be made by methods Accelerated Shelf Life Testing (ASLT). In principle, this method is storing food products at extreme temperatures. Determining the shelf life of shrimp paste powder using a combination treatment temperature (30oC and 40oC) and packaging (aluminum foil and plastic HDPE). The results of research determining the shelf life of shrimp paste powder method Accelerated Shelf Life Testing (ASLT) obtained the best treatment at storage temperature of 40oC with aluminum foil packaging is 1 year 6 months 28 days, whereas at 30 ° C with aluminum foil packaging is 1 year 1 month 13 days , Storage at 40 ° C by using HDPE packaging that is 3 months and 22 days, and storage at 30 ° C is 2 months and 20 days.